Design of Wiper Cleaner Prototype based on IoT for Solar Panels With Rooftop Installation - Fitriana Fitriana; Darma Arif Wicaksono; Sofia Ariyani; Rais Nurwahyudin; Fahmi Aulia Ajie (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
Many factors that affect the efficiency of solar panels, one of which is environmental factors. Among the environmental factors that negatively affect the solar panels performance is the dust accumulation on the top surface of the solar panels. This is because dust will block solar radiation from entering directly into solar cells and can reduce the efficiency of solar panels. In this research, a wiper cleaner prototype has been designed to clean dust on solar panels with a rooftop installation. This wiper cleaner system is made by utilizing servo motor movement and Internet of Things (IoT) technology so that it can be controlled remotely using an android. This wiper cleaner prototype works with a response time of 1 second and a speed of 0.0254 m/s. The wiper cleaner control system via Android can work with a maximum range of 30 meters. In addition, based on research that has been done shows that wiper cleaner can increase the efficiency of solar panels by 8.5%.